Barriers Constraining the Low and Middle Income Housing Finance Market in Bangladesh - Khare, Harish S. (International Finance Corporation, Washington, D.C., 2017)
The study aims to assess the market for low and middle income housing finance in Bangladesh and identify the demand trajectory of this segment over the next 4 years. In addition, the report identifies factors that constrain the housing finance from serving low and middle income households.